A Multi-standard Approach for GIAO 13C NMR Calculations - Sarotti, Ariel Marcelo (2009)
The influence of the reference standard employed in the calculation of 13C NMR chemical shifts was investigated over a large variety of known organic compounds, using different quantum chemistrymethods and basis sets. After detailed analysis of the collected data, we found that methanol and benzene are excellent reference standards for computing NMR shifts of sp3- and sp-sp2-hybridized carbon atoms, respectively. This multi-standard approach (MSTD) performs better than TMS in terms of accuracy and precision and also displays much lower dependence on the level of theory employed. The use of mPW1PW91/6-31G(d)//mPW1PW91/6-31G(d) level is recommended for accurate 13C NMR chemical shift prediction at low computational cost.